Impedance model of trap states for characterization of organic semiconductor devices - Burtone, L; Ray, D; Leo, K; Riede, M (American Institute of Physics, 2012)
An equivalent circuit to characterize energy distribution of trap states present in organic semiconductors by impedance spectroscopy is proposed. We analyze the impedance spectra of a small-molecule organic solar cell and observe the contribution of trap states at low frequencies. Starting from previously reported equivalent circuits and a theoretical model based on the integration of a general traps distribution, we develop an equivalent circuit, which is able to describe the energetic distribution of trap states typically observed in organic semiconductors. The experimental data can be reproduced by our equivalent circuit, and we estimate a density of trap states in a Zn-phthalocyanine:C60 bulk heterojunction to be about 1.9 ± 0.6 × 1016 cm−3 eV−1. © 2012 American Institute of Physics.